Sapa Tana Program: A Community Empowerment-Based Waste Management Program in Tana Duen Village - Raden Roro Seraphine Kalista Drupadi (Prospect Publishing, 2025)
Waste management has become a significant challenge in Tana Duen Village, Sikka Regency, East Nusa Tenggara Province, due to the absence of a structured system. The Sapa Tana program was designed using the Asset-Based Community Development (ABCD) approach by optimizing community-owned human, social, environmental, physical, and financial assets. This article aims to formulate a waste management strategy that not only focuses on environmental aspects but also generates social and economic value. The analysis shows that the stages of discovery, dream, design, define, and destiny can strengthen community participation, enhance the productivity of targeted groups, and promote the creation of a sustainable waste management system. The program also opens opportunities for income generation through the exchange of plastic waste and the utilization of compost. Furthermore, Sapa Tana fosters collective awareness to protect the environment and strengthen social solidarity. Through cross-sector collaboration involving village government, local agencies, and community groups, Sapa Tana has the potential to become a community empowerment model that is responsive to local contexts, nurtures a sense of ownership, and can be replicated in other regions facing similar challenges.